2004
DOI: 10.1111/j.0031-9317.2004.00396.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenylalanine ammonia‐lyase‐induced freezing tolerance in jack pine (Pinus banksiana) seedlings treated with low, ambient levels of ultraviolet‐B radiation

Abstract: Phenylalanine ammonia-lyase (PAL) induction in UVBexposed plants leads to an increased synthesis of UV-absorbing phenols. As phenols, including anthocycanins, are linked to many protective mechanisms in plants, we tested the hypothesis that UVB-induced phenol accumulation, mediated by PAL, may confer freezing tolerance in jack pine (Pinus banksiana Lamb) seedlings. The hypothesis was tested by applying UVB in the presence and absence of the PAL-inhibitor, 2-aminoindan-2-phosphonic acid (AIP). Jack pine seedlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 50 publications
2
33
1
Order By: Relevance
“…It has recently been shown that inhibition of the key enzyme of the phenolic pathway, phenylalanine ammonia-lyase (PAL), and the subsequent deficiency of phenolics impaired the course of cold acclimation in many ways (Solecka and Kacperska 2003). This is in agreement with the study of Teklemariam and Blake (2004), which showed that the freezing injury of jack pine (Pinus banksiana) seedlings was increased in PAL-inhibited seedlings. Thus, the strong increase of total phenolics in our study, from 9% to 24% of needle DW during the course of cold hardening, may indicate their importance also for freezing tolerance of spruce.…”
Section: Discussionsupporting
confidence: 65%
“…It has recently been shown that inhibition of the key enzyme of the phenolic pathway, phenylalanine ammonia-lyase (PAL), and the subsequent deficiency of phenolics impaired the course of cold acclimation in many ways (Solecka and Kacperska 2003). This is in agreement with the study of Teklemariam and Blake (2004), which showed that the freezing injury of jack pine (Pinus banksiana) seedlings was increased in PAL-inhibited seedlings. Thus, the strong increase of total phenolics in our study, from 9% to 24% of needle DW during the course of cold hardening, may indicate their importance also for freezing tolerance of spruce.…”
Section: Discussionsupporting
confidence: 65%
“…The protection of the photosynthetic apparatus against the photoinhibition generally associated with chilling stress could be detected not only in the temperature-and pH-dependent activation of the xanthophyll cycle, involved in energy dissipation, and in an increase in the pH-independent carotenoid content, but also as an increase in the quantity of phenoloids, flavonoids and anthocyanins synthesised via the phenylpropanoid pathway [29][30][31]. When changes in the quantities of the phenoloids (hydroxycinnamic acid derivatives, ferulic acid esters, p-coumaric acid) and flavonoids (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This reaction is catalyzed by the enzyme PAL, which is commonly considered the principal enzyme in the biosynthesis of phenolic compounds (Dixon and Paiva 1995). In previous investigations, PAL activity could be induced by various stresses, such as chilling (Sanchez-Ballesta et al 2000;Lafuente et al 2003), wounding (Campos-Vargas et al 2005), UV-B light (Teklemariam and Blake 2004), ozone (Sgarbi et al 2003), pathogen invasion (Jones 1984) and plant hormones including jasmonic acid, salicylic acid and ethylene (Lafuente et al 2004;Wen et al 2005;Chen et al 2006). The present study showed that application of 150 lM exogenous SA induced a rapid and substantial increase in PAL activity in grape berry tissues during high temperature stress, within 1 h of heat treatment which alleviated the injury caused by high temperature stress (Fig.…”
Section: Discussionmentioning
confidence: 99%